Effectiveness of oral cholera vaccine in preventing cholera among fishermen in Lake Chilwa, Malawi: A case-control study. Issue 28 (19th June 2019) - Grandesso, Francesco; Kasambara, Watipaso; Page, Anne-Laure; Debes, Amanda K.; M'bang'ombe, Maurice; Palomares, Adriana; Lechevalier, Pauline; Pezzoli, Lorenzo; Alley, Ian; Salumu, Leon; Msyamboza, Kelias; Sack, David; et al.
Highlights: Oral cholera vaccine producers recommend to keep the vaccine vials at 2–8 °C. So far oral cholera vaccine campaigns followed producers' recommendations. In Lake Chilwa second vaccine dose was kept at room temperature for two weeks. This study showed high short-term effectiveness after such vaccine campaign. Results was comparable to campaigns that stored both vaccine doses at 2–8 °C. Abstract: Background: In response to a cholera outbreak among mobile, difficult-to-reach fishermen on Lake Chilwa, Malawi in 2016, a novel vaccine distribution strategy exploited the proven vaccine thermostability. Fishermen, while taking the first vaccine dose under supervision, received the second dose in a sealed bag, and were told to drink it two weeks later. This study assessed short-term vaccine protection of this strategy. Methods: Patients with diarrhoea admitted to health facilities around lake were interviewed and a stool sample collected for PCR testing. Vaccine effectiveness was assessed in a case-control test-negative design by comparing cases (PCR-positive for V. cholerae O1) and controls (patients with diarrhoea but PCR-negative) and with the screening method that compared the proportions of vaccinated among cholera cases versus the general fishermen population. Results: Of 145 study participants, 120 were fishermen living on the lake. Vaccine effectiveness at three-months was 90.0% [95% CI: 38.8; 98.4] among fishermen and 83.3% [95% CI: 20.8; 96.5] among all participants in the case-control test-negative design, and 97.5% [95% CI: 90.9; 99.3] with the screening method. Conclusion: This strategy was effective in providing short-term protection in fishermen against cholera. Further research is needed to determine the adding value of the second dose and to identify the optimal vaccination strategies for different contexts.